1987
DOI: 10.1002/jcp.1041320307
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic evaluation of human endothelial cell cultures

Abstract: Cytogenetic evaluation of serially subcultivated human endothelial cells revealed significant differences between cultures derived from fetal umbilical cords and cultures derived from various vessel sites in adults. A rapid increase in the prevalence of polyploid cells, to levels of 100% in many cases, was detected in human umbilical vein endothelial cell cultures but not in endothelial cell cultures from adult vessels. Because the development of polyploidy has been viewed as one signpost of in vitro senescenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

1989
1989
2004
2004

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 40 publications
(42 reference statements)
1
20
0
Order By: Relevance
“…Perhaps the trisomy 11 can act in concert with several other trisomies, or the other trisomies result from a general process that randomly increases the frequency of nondisjunction. Nichols et al (1987) found high levels ofpolyploidy in cell lines derived from umbilical cords (loo%), but only a moderate increase in the adult cell lines. Perhaps because of improved techniques in isolation and culturing (Levine, unpublished data), our adult endothelial lines appear t o proliferate longer in culture and undergo more CPDLs than those studied by Nichols et al (1987).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Perhaps the trisomy 11 can act in concert with several other trisomies, or the other trisomies result from a general process that randomly increases the frequency of nondisjunction. Nichols et al (1987) found high levels ofpolyploidy in cell lines derived from umbilical cords (loo%), but only a moderate increase in the adult cell lines. Perhaps because of improved techniques in isolation and culturing (Levine, unpublished data), our adult endothelial lines appear t o proliferate longer in culture and undergo more CPDLs than those studied by Nichols et al (1987).…”
Section: Discussionmentioning
confidence: 97%
“…Nichols et al (1987) found high levels ofpolyploidy in cell lines derived from umbilical cords (loo%), but only a moderate increase in the adult cell lines. Perhaps because of improved techniques in isolation and culturing (Levine, unpublished data), our adult endothelial lines appear t o proliferate longer in culture and undergo more CPDLs than those studied by Nichols et al (1987). This may account for the higher levels of polyploidy in some of the adult EC cultures analyzed and the increased frequency of trisomy 11 seen in the current study.…”
Section: Discussionmentioning
confidence: 97%
“…However, trisomic clones may also arise in cultures of cells from individuals without cancer. Nichols et al (1987) found tri somy 11, as well as a deletion of 13q, in a culture of endothelial cells from the abdominal aorta. The latter observation clearly shows that caution should-be exercised in the interpretation of chro mosome changes in cultures derived from tumor tissue.…”
mentioning
confidence: 99%
“…Chromosome 13 monosomy is associated with LOH, and an increase in migratory and presumably proliferative capacity-a phenomenon suggesting clonal expansion and survival advantage under HUVEC culture conditions. Aneuploidy has been observed by others (Nichols et al 1987;Johnson et al 1992) and us (Zhang et al 2000) in cultured VECs from human donors. However, other studies found that the common feature of aneuploidy in cells derived from different donors was the development of polyploidy in late passages (Saksela and Moorhead 1963;Benn 1976).…”
Section: Discussionmentioning
confidence: 81%
“…Aneuploidy, i.e., the state of loss or gain of chromosomes, is frequently observed in cultured human cells, including human vascular endothelial cells (VECs) (Saksela and Moorhead 1963;Benn 1976;Nichols et al 1987;Casalone et al 1992;Johnson et al 1992;Kehrer et al 1994;Mukherjee and Costello 1998). However, this phenomenon is primarily observed in presenescent cultured cells.…”
Section: Introductionmentioning
confidence: 98%